Analisis produksi pembudidaya ikan di kawasan minapolitan di kecamatan malinau utara kabupaten malinau (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
Malinau District as an autonomous region that is relatively new to have a huge potential in the field of fisheries management, this is evidenced by the establishment of the Decree of the Minister of Marine and Fisheries which set Malinau District as Minapolitan Region. This study was included in the category of quantitative research , which attempts to explain the influence and test the relationship that occurs between capital, labor and a vast pool to the production of fish farmers in Region Minapolitan Malinau District. In the first hypothesis test, the results showed a value of 178.389 F count > F table of 8.81 means that there is no significant influence variable capital, labor and the vast pool of fish production. In the second hypothesis testing, the results showed t value of 1.168 < F table of 2.2 means that there is no significant influence on the production of variable capital. In the third hypothesis testing, the results showed t value of 0.650 < F table of 2.2 means that there is no significant effect of variable labor to the production of fish. In the fourth hypothesis testing, the results showed t value amounted to 10.087 > F table of 2.2 means that there is no significant influence of the variable vast pool of fish production.